THE INDONESIA BEST SUSTAINABILITY REPORT AS A STUDENTâS ACCOUNTING TOOL TO UNDERSTAND CSR CONCEPT - Sihombing, Ranto P. (Jurnal Dinamika Akuntansi, 2015)
Guideline Reporting Initiatives has long become the guidance for making sustainability report (SR).Â It contains the companyâs Corporate Social Responsibilities (CSR) activities. By using these guidelines, the CSR activities of the company can be focused on and directed to minimize the negative impact. CSR activities will be grouped into three bottom lines of activities that are profit, people and planet. SR analyzed were the ones from companies associated with the exploration of natural resources which are the best in publishing the reports and conducting the CSR programs. The data obtained from questionnaire and interviews of accounting students from environmental and social accounting class in which there are also students from Slovenia, Lithuania and Ukraine. The results of this study found that students can understand easily the meaning of CSR in a comprehensive manner. They know both aspect of disclosure and report of the sustainability report.